Effect of Age and Frequency of Collection on Quality of Jersey Bulls Semen at National Livestock Breeding Center (NLBC), Nepal - Sankhi, S.; Sapkota, K.R.; Regmi, B. (International Journal of Applied Sciences and Biotechnology, 2019)
Objective: To determine the effect of age and frequency of collection on quality parameters of Jersey bull semen at National Livestock Breeding Center (NLBC), Pokhara. Materials and Methodology: Nine Jersey bulls were selected randomly from NLBC. To obtain the effect of age, six bulls of three different age interval (3-4, 5-7 and 8-9 years) were selected randomly. Remaining three bulls were used to determine the effect of frequency of collection on semen quality. Studies were conducted for three months (Nov/Dec to Dec/Jan, 2016). Semen quality was analyzed using CASA system and SMILE software. ANOVA and paired t- tests were applied to find out level of significance. All the statistical analyses were done using SPSS 17.0 Results: Sperm concentration, post- thaw motility, live sperm, and abnormal sperm were significantly affected by the age of the bulls. Semen quality was found superior in the bulls belonging to 5-7 years of age intervals. Significantly higher value for semen volume, sperm concentration and post- thaw motility was obtained on second collection (P<0.05). However, volume initial motility, pre-filling motility, live sperm and abnormal sperm percentage did not differ significantly among different age intervals and between the frequencies of collection. Conclusion: Different quality parameters of semen like volume, concentration, initial motility, pre-filling motility, post thaw motility, live and normal spermatozoa percentages were higher in 5-7 years old bulls and in second collection of semen. Int. J. Appl. Sci. Biotechnol. Vol 7(1): 88-95